Examining the Relationship between Socio-Emotional Competence and Speaking Skills in EFL Learners - Nurpratiwi, Fheby Indriyanti; Afiyattena, Nurul; Nurhaliza, Siti (Lembaga Sosial Rumah Indonesia, 2026)
Purpose – Although students’ speaking skills have been has been widely discussed from cognitive and instructional perspectives, empirical evidence on its relationship with socio-emotional competence in EFL junior high school contexts remains limited. This study aims to examine the relationship between students’ socio-emotional competence and their speaking skills in an EFL classroom.Methods – This study employed a quantitative correlational design involving 30 seventh-grade EFL students at rural private junior high school. Data were collected using a socio-emotional competence questionnaire and a speaking skill test and were analyzed using Pearson Product–Moment correlation. Findings – The analysis revealed a moderate and statistically significant positive relationship between socio-emotional competence and speaking skill (r = 0.452, p < .05). It signifies that socio-emotional competence functions as a meaningful psychosocial resource that supports speaking performance rather than as a direct determinant. The statistically significant association reinforces the view that speaking skill is not merely a cognitive-linguistic outcome but is co-constructed through emotional regulation, social interaction skills, and self-awareness. However, the results do not imply a causal relationship between the variables. Research Implications – The findings suggest that socio-emotional competence is meaningfully associated with students’ speaking skill and therefore deserves attention in the design of speaking instruction. Teachers may integrate collaborative tasks, confidence-building activities, and emotional awareness strategies to support students’ oral participation. However, this study with a small sample size and the focus on a single junior high school context limit the generalizability of the finding. Future studies with larger samples and experimental designs are recommended to explore potential causal mechanisms across different educational settings.